The Directions and Names of the Winds: [Aristotle], Ventorum situs et nomina - Bowen, Alan C. (Aestimatio)

(untitled) (Institute for Research in Classical Philosophy and Science, 2020)
The anonymous text Ventorum situs et nomina, once held to be by Aristotle himself, gives the local names of 10 topic winds as well as their directions. It is not an elaboration of the wind-rose that Aristotle, for example, describes in Meteor. 2.5, though many scholars have assumed this, but a presentation of a weather-map for the inhabited world (οἰκουμένη). What seems to be important to the author in collecting the local winds under the topic winds is not so much their direction as their time of year as well as the etymologies of the local names.